2016
DOI: 10.1002/14651858.cd012209
|View full text |Cite|
|
Sign up to set email alerts
|

Serious Gaming and Gamification interventions for health professional education

Abstract: This is the protocol for a review and there is no abstract. The objectives are as follows: To evaluate the effectiveness of Serious Gaming and Gamification interventions for delivering pre- and post-registration health professional education compared with traditional learning, other types of eLearning, or other Serious Gaming and Gamification interventions. We will primarily assess the impact of these interventions on students' knowledge, skills, professional attitudes and satisfaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…We report our reviews in line with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) reporting guidelines [9]. Correspondingly, we first developed and published or registered protocols and then embarked on systematic reviews [13,15-19,23]. We present our methodological approach below.…”
Section: Digital Health Education Collaboration For Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…We report our reviews in line with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) reporting guidelines [9]. Correspondingly, we first developed and published or registered protocols and then embarked on systematic reviews [13,15-19,23]. We present our methodological approach below.…”
Section: Digital Health Education Collaboration For Evidence Synthesismentioning
confidence: 99%
“…On the other hand, there are potential disadvantages such as implementation restrictions caused by digital divide (requirement of information technology infrastructure and digital literacy); additional development and set-up costs; and untoward effects of digital education such as anxiety, dizziness, and isolation. We were unable to find a robust framework that would capture and describe the variety of digital education applications in health, particularly in relation to the employed technology, which we termed “modalities.” Through discussion with educational experts within our teams and review of relevant literature, we identified the following modalities: mobile learning (m-learning) or mobile digital education [13,24], virtual reality [19,22], virtual patient [16], serious gaming and gamification [15,27], offline or online digital education [17,18], massive open online courses [28], digital psychomotor skills trainers [29], and virtual learning environment [30]. Operational definitions for these modalities are presented in Table 1.…”
Section: Defining the Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Given the lack of research and consolidated knowledge about this teachinglearning approach [38], both quantitative and qualitative findings arising from this study will provide important theoretical and pragmatic insights to others developing immersive simulation, or virtual reality opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Medical education research has found largely positive results regarding the use of gamification as a teaching-learning mechanism, in terms of medical content validity [27], acceptance of and retention of learned knowledge [44], and ongoing skill retention and learner engagement [29,45]. The growing importance and interest in this topic can also be inferred from the recent registration of a Cochrane Database of Systematic Review protocol, which plans to examine the effectiveness of serious gaming and other gamified interventions in health professional education [38]. As outlined by Cant and Cooper [41], this type of clinical education pedagogy will likely "have a major place in nursing curricula in the next decade"(p1441), and therefore warrants further examination by clinician educators.…”
Section: Discussionmentioning
confidence: 99%